Death and Migration: Migrant Journeys and the Governance of Migration During Europe's "Migration Crisis". Issue 2 (June 2021) - McMahon, Simon; Sigona, Nando
In migration and refugee studies, migrant deaths have frequently been closely linked to contemporary forms of border and migration governance. Migrant deaths at sea have also played a central role in shaping policy and public responses to Europe's "crisis." Yet relatively little scholarly work has analyzed migrants' personal experiences related to death and the impact of these experiences on their mobility. Drawing on 500 semi-structured interviews with people who crossed the Mediterranean Sea by boat in 2015–2016 and over 100 interviews with key stakeholders in the region, this article documents geographies of violence and death stretching throughout migration trajectories that start far from the Mediterranean shores. It shines light on the different ways that encountering the deaths of others and perceiving the inevitability of one's own death drive and shape migration decisions and journeys. The article also highlights differences between European policy responses to migrant deaths and the experiences of those migrants making the journey. In doing so, it calls for a more expansive understanding of the relationship between migrant deaths, policies, and migration that extends beyond the relatively small parcel of water that divides Europe from its southern and eastern neighbors.